Shaken and stirred: emotional state, cognitive load, and performance of junior residents in simulated resuscitation - Van Heer, Shyan; Cofie, Nicholas; Gutiérrez, Gilmar; Upagupta, Chandak; Szulewski, Adam; Chaplin, Timothy (Canadian Medical Education Journal, 2021)
Background: Patient resuscitation can be overwhelming for junior postgraduate medical residents due to its inherent complexity and high-stakes environment. Emotional states of unpleasant hyperarousal burden cognitive resources, contributing to cognitive overload and performance decline. Our objective is to characterize the associations between pre-scenario emotional state and junior residents’ cognitive load and performance in a simulated-resuscitation, to provide evidence for informed curricular development. Methods: PGY-1 residents self-rated their emotional state before four simulated-resuscitation scenarios, and their cognitive load after. Faculty assessed performance with entrustment scores. Factor analysis identified the principal components of emotional state data. Linear regression models examined the relationship between pre-scenario emotional components, cognitive load, and performance scores. Results: 47/47 medical and surgical residents (100%) participated and completed Emotional State (99.5%) and Cognitive Load (98.9%) surveys. Positive invigoration and negative tranquility were the principal components. Pre-scenario tranquility was negatively associated with cognitive load (b= -0.23, p < 0.0001), and cognitive load was negatively associated with performance scores (b= -0.27, p < 0.0001). Pre-scenario invigoration was negatively associated with cognitive load (b=-0.18,p = 0.0001), and positively associated with performance scores (b= 0.08, p = 0.0193). Conclusion: Amongst junior residents participating in simulated resuscitation scenarios, pre-scenario agitation (negative tranquility) is associated with increased cognitive load, which itself is associated with lower performance scores. These findings suggest residency programs should consider developing curriculum aimed at modulating residents’ emotional agitation and reducing residents’ cognitive burden to improve resuscitation performance.